ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN DI PULAU JAWA TAHUN 2014-2020 - Andina, Resta Dwi; Jajang, jajang; Supriyanto, Supriyanto (Universitas Jenderal Soedirman, 2021)
ABSTRACT. Unequal distribution of income is one indicator of community welfare. Improving and equalizing the standard of living people in various regions is one of the efforts to realize national economic development. The existence of an unequal distribution of income also has an impact on economic development. This study discusses panel data regression analysis to determine the factors that affect the unequal distribution of income in Java from 2014 to 2020 with the help of Eviews 10 software. The factors that are thought to affect unequal distribution of income in this study are the human development index, open unemployment rate, regional gross domestic product per capita, and total of poor people. The fixed effects model (FEM) was chosen to be the best model. The results showed that the HDI and RGDP per capita variables had negative and significant effect on unequal distribution of income in Java from 2014 to 2020.Keywords: panel data regression, fixed effect model, unequal distribution of income, gini ratio. ABSTRAK. Ketimpangan distribusi pendapatan merupakan salah satu indikator kesejahteraan masyarakat. Meningkatkan dan menyetarakan taraf hidup masyarakat di berbagai daerah merupakan salah satu upaya mewujudkan pembangunan ekonomi nasional. Adanya distribusi pendapatan yang tidak merata berdampak pada pembangunan ekonomi. Penelitian ini membahas analisis regresi data panel untuk mengetahui faktor-faktor yang mempengaruhi ketimpangan distribusi pendapatan di Pulau Jawa tahun 2014 sampai 2020 dengan bantuan software Eviews 10. Faktor-faktor yang diduga mempengaruhi ketimpangan distribusi pendapatan dalam penelitian ini yaitu indeks pembangunan manusia, tingkat pengangguran terbuka, produk domestik regional bruto perkapita, dan jumlah penduduk miskin. Fixed Effect Model (FEM) terpilih menjadi model terbaik. Hasil penelitian menunjukkan bahwa indeks pembangunan manusia dan produk domestik regional bruto perkapitadan PDRB perkapita berpengaruh negatif dan signifikan terhadap ketimpangan distribusi pendapatan di Pulau Jawa tahun 2014 sampai 2020.Kata kunci: regresi data panel, model fixed effect, ketimpangan distribusi pendapatan, rasio gini